Genetic diversity and haplotype distribution of Pachymeniopsis gargiuli sp. nov. and P. lanceolata (Halymeniales, Rhodophyta) in Korea, with notes on their non-native distributions - Kim, Su Yeon (Journal of phycology, 2014)
© 2014 Phycological Society of America.